Testing and evaluation of the coconut oil expeller for Jatropha Curcas seeds - Rodulfo, Victor A. Jr (Philippine agricultural mechanization journal)
The UPLB Fresh Dry Coconut Oil Milling System was tested and evaluated using Jatropha seeds as feedstock. The screw type oil expeller was particularly evaluated in terms of the following operating conditions : crushed and whole seeds; hulled and dehulled seeds; varying moisture content and temperature of the feedstock; and varying speed of the expeller screw. The test and evaluation were conducted to determine the extraction rate, efficiency and cost to produce crude oil. The performance of the oil expeller was affected by the machine adjustment and conditions of the seed.